PENGARUH KUALITAS SITUS WEB PERSEPSIAN DAN KONTROL PERILAKU PERSEPSIAN TERHADAP NIAT DAN AKTIVITAS BELANJA ONLINE: RISIKO PERSEPSIAN DAN KEPERCAYAAN SEBAGAI MEDIASI - Christian Daniel Manu (Akademi Akuntansi YKPN Yogyakarta, 2016)
Website has been online business environment that makes transactions is easy to completed. The quality of the website should be a concern for companies that do business online. Individuals who shop online have the expectation that the quality of the website must be trusted and able to reduce individual risk perception in the transaction. Individual's ability to performon line transactions through the use of web-based technologies have also been developed. The theory of planned behavior and technology acceptance model used as basic theories in the proposed development of a model for measuring the activity of online shopping. A total of six constructs used in this research model. Constructs of online shopping is expected to be affected by intention to shopping and self-efficacy. Then, construct intention to shopping is predicted to be affected by website quality, trust, and perceived risk. The 729 data obtained through an online survey was used to test the model by using a statistical tool structural equation modeling (SEM). The findings of this study indicate that the developed model is marginal fit to explain the influence of website quality and perceived behavioral control on intentions and activities of online shopping, with the perceived risk and trust as a mediator. Development of website features and strategies to develop the self-efficacy of individuals is the implications of this research. Keywords: Theory of Planned Behavior, Technology Acceptance Model, Website Quality, SelfEfficacy, Trust, Perceived Risk, Intention, Online Shopping.